2006
DOI: 10.1021/jm0603318
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical Diversity-Oriented Conformational Restriction Strategy. Development of Potent Histamine H3and/or H4Receptor Antagonists with an Imidazolylcyclopropane Structure

Abstract: The stereochemical diversity-oriented conformational restriction strategy can be an efficient method for developing specific ligands for drug target proteins, especially in cases where neither the bioactive conformation nor the pharmacophore is known. To develop potent H3 and H4 receptor antagonists, a series of conformationally restricted analogues of histamine with a chiral cis- or trans-cyclopropane structure were designed on the basis of this strategy. These target compounds with stereochemical diversity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 32 publications
(44 reference statements)
1
44
0
Order By: Relevance
“…(5) UR-PG80 [50] 5.53 § 7.11* < 5 § < 5 § (6) UR-AK478 [50] < 6 § 7.51* < 5 § 8.07* (7) Thioperamide < 5 < 4 7.3 7.2 (8) JNJ7777120 [70] 6.01 5.07 5.65 7.92 (9) Imidazolylcyclopropane [51] 5.07 ‡ < 5 ‡ 8.07 ‡ 6.07 ‡ (10) Dibenzodiazepine [76] 8.11 5.06 5.04 7.55…”
Section: The Histamine Receptors and Molecular Modeling Of Histamine mentioning
confidence: 99%
See 1 more Smart Citation
“…(5) UR-PG80 [50] 5.53 § 7.11* < 5 § < 5 § (6) UR-AK478 [50] < 6 § 7.51* < 5 § 8.07* (7) Thioperamide < 5 < 4 7.3 7.2 (8) JNJ7777120 [70] 6.01 5.07 5.65 7.92 (9) Imidazolylcyclopropane [51] 5.07 ‡ < 5 ‡ 8.07 ‡ 6.07 ‡ (10) Dibenzodiazepine [76] 8.11 5.06 5.04 7.55…”
Section: The Histamine Receptors and Molecular Modeling Of Histamine mentioning
confidence: 99%
“…Because of the therapeutic relevance of H 3 R, a lot of studies describing SARs of H 3 receptor ligands are found in literature [51][52][53][54]. To increase understanding of pharmacology of H 3 R ligands on a molecular level, numerous molecular modeling studies were performed.…”
Section: The Histamine H 3 Receptor and Its Ligandsmentioning
confidence: 99%
“…The pendant pharmacophore groups, the imidazole ring and the hydrophobic 4-chlorobenzyl moiety, are projected in various three dimensional arrangements due to the chiral cis-and transcyclopropane central spacer scaffold. The (1R,2S)-trans-cyclopropane isomer 162 had comparable antagonism of H 3 and H 4 receptors, whereas the (1S,2R)-trans-cyclopropane isomer 163 was a highly selective antagonist for H 3 receptor as shown inFigure 68 201. Therefore, one can achieve receptor subtype potency and selectivity by modifying the molecular configuration at the cyclopropane spacer scaffold.…”
mentioning
confidence: 99%
“…This approach to the design of biologically relevant molecules is referred to as diversity-oriented conformational restriction. 3,4 The idea has been widely used in the design of conformationally restricted amino acids and diamines, 5 whereas conformationally constrained amino sulfonyl chlorides has received much less attention. The limited long-term stability of the latter compounds and some of their derivatives may be one of the reasons for this.…”
mentioning
confidence: 99%